The Case Writer's Toolkit - Gwee, June (Springer Singapore, 2018)
This book deconstructs the case study, describes the case writing process and explains how a good case study is composed. It is a reference book that accompanies case writers on their case writing journey. It serves as a guide for writers to develop case studies for teaching, research, and knowledge-capture. There are illustrations and charts to help writers visualise concepts, signpost ideas, break down complex information and apply techniques in a practical manner.